Open access encyclopedia: an important component of knowledge infrastructure (Pubmet, 2023)
Since the era of Enlightenment, the role of encyclopaedias has been to organise and structure knowledge, and communicate it to society. In the digital age, professionally edited encyclopaedias have not lost its enlightenment mission; on the contrary, its role in enabling systemic and reliable orientation within the ever-increasing amount of data and information is even more emphasised. By entering the digital age the functionality and usability of encyclopaedias are enhanced enormously. Digital technologies transformed the ways in which encyclopaedic knowledge is prepared, organised and presented, and more importantly facilitated its distribution, accessibility and usage (Jermen & Jecić, 2018; Jermen & Jecić, 2020).Professionally edited open access national encyclopaedias contribute to raising the level of public knowledge by dissemination of reliable and verified information in users’ mother tongue. They provide a connection between experts and average citizens, acting as an important science communication tool, and as such should be at the core of the research and didactic infrastructure of any modern society (Jecić & Jermen, 2020). Furthermore, in fierce competition with various, often unreliable online information sources, they could also play an important role in the struggle against the speedy growth of disinformation and misinformation (Bentzen, 2018).As one of the prominent examples of the importance of encyclopedistics in the modern age is the very existence of the Miroslav Krleža Institute of Lexicography in Croatia, a publishing house and a scientific institution, which is defined in the governmental act as a “public institution of relevance for the Republic of Croatia''. With the mission to systematise and disseminate scientifically verified knowledge in the broadest span of scientific disciplines, its publications (encyclopaedias, encyclopaedic monographs, lexicons, dictionaries, etc.), targeted for a broader audience, as well as specialists, have been produced in collaboration with numerous high-profile researchers from academia since its foundation in 1950. Since 2008, the Institute has been developing freely accessible collections of digital encyclopaedic editions, which currently comprise approximately 270,000 articles. A great number of Institute’s editions (along with the additional digital content) that are available in open access surely contributes to their increased visibility (more than 15 million page views in 2022) and hence the potential for creating societal impact.This presentation aims to provide an overview of the development of lexicography and encyclopedistics in the digital environment, primarily from the perspective of the Miroslav Krleža Institute of Lexicography. It places special emphasis on the Institute's open access publishing efforts over the past 15 years. Considering the fact that there are still no dedicated open access publishing schemes for books in Croatia, and that open access still represents a relatively small part of the book publishing landscape in Europe (Gimenez-Toledo et al. 2022), the Institute's endeavours in this area have been rather innovative. Along with the dissemination of scientifically verified information, open access encyclopaedias give the possibilities of linking to the digital data and collections of other research and cultural institutions, thus serving as the important component of digital knowledge infrastructure (Jermen & Jecić, 2018). Thanks to this increased connectivity, the Institute has taken part in several projects, initiatives, and communities, both in Croatia and abroad, which will be described in this presentation.